UNO and the promotion of the human rights in Africa : The case of French-speaking sub-Saharan Africa. - (:unkn) unknown (My University, 2017)
The present reflection on the framework of intervention of UNO in the field as of human rights, in French-speaking sub-Saharan, pursues two principal goals. The primary goal aims at showing that the United Nations Organization is very committed on the ground of the human rights, in the countries of French-speaking space. This commitment is not new. Since 1960, year of the deployment of the first Operation of peacekeeping in French-speaking sub-Saharan Africa, the Operation of UNO in Congo (ONUC), the United Nations did not cease considering political stability, economic and social of Africa, like priority and the principal condition of the peacekeeping and the securty international. This stability passes by the creation of the effective conditions of promotion and protection of the basic rights of the African citizens. We tried, within the framework of this work to appreciate the assessment of UNO in the field as of the human rights. However, after 56 years of presence in sub-Saharan French-speaking Africa, this asssessment apears mainly negative. The second objective of this work is to analyze more precisely this failure and to understand the causes of them. Indeed, the programmes of promotion of the humlan rights, aiming inculcating a culture of respect of the human rights within the various social and economic categories and at reinforcing the capacities of the States in the field of the human rights are often unsuited to sociocultural réalities of Africa, insofar as they do not take into account, the fundamental causes of the African civil wars, that constitutite the intercommunity conflicts.
Keywords: African Research